Penile strangulation due to metallic ring: a surgical emergency - Saroj, Jitendra Kumar; Ahmad, Arshad; Sachan, Ankit; Yadav, Ganesh (International Surgery Journal, 2019)
Penile strangulation is a very rare but most serious clinical condition. It usually results from positioning of any foreign object at base of penis for sexual stimulation. If urgent intervention is not done this may lead to serious complications even death? In this study usual common method were unsuccessful therefore partial penectomy was done.